Ketika Tren Menjadi Peluang : Analisis Sosiologi Ekonomi Atas Perilaku Bisnis Gen Z di Era Digital - Nur Syafika; Aini Nurpratiwi; Lukman Ismail; Nasriah Nasriah (Journal of Management and Social Sciences, 2025)
The digital era has brought significant changes to various aspects of human life, including business behavior among the younger generation, especially Generation Z. This generation, which grew up amidst technological advances, has special characteristics, such as high dependence on digital technology, rapid adaptability, and a tendency to take advantage of trends to create business opportunities. This study aims to understand the phenomenon of Generation Z business behavior in the digital era through a qualitative approach with a literature study method. The results of the study show that Generation Z is not only a passive consumer, but also an innovator who utilizes digital platforms to overcome global economic challenges. Using an economic sociology approach, this study explores various social, cultural, and economic factors that influence their business behavior. In addition to offering opportunities, digital transformation also brings challenges in the form of competition between platforms that require adaptive strategies from business actors. This study emphasizes the importance of strategic responses that are in line with Generation Z's values ​​and preferences to achieve sustainability in the modern era.